If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x) + -1ln(6) = (16) Multiply ln * x lnx + -1ln(6) = (16) Reorder the terms for easier multiplication: lnx + -1 * 6ln = (16) Multiply -1 * 6 lnx + -6ln = (16) Reorder the terms: -6ln + lnx = (16) -6ln + lnx = 16 Solving -6ln + lnx = 16 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -16 + -6ln + lnx = 16 + -16 Combine like terms: 16 + -16 = 0 -16 + -6ln + lnx = 0 The solution to this equation could not be determined.
| 3(2x+4)=5(x-4) | | -4(2y+4)-1=-4(y+8)+2y | | 12a^6-8a^3= | | -3x-34(x+3)=-9(4x+2) | | 2x+1x=3 | | 4(x+3)+9=13 | | 6z+2=1 | | -2x+25=9 | | ln(2x+9)+ln(3)=2ln(x) | | -3(4-5Y)=7y+4 | | x^4-8x^2+9=0 | | -10=8-(9-A) | | 20=5-(Z+6) | | 20=5-z+6 | | -5(4+r)=25 | | -7+[(1-11)-(-1-3)]= | | 5x-9+5x=-29 | | -7[(1-11)-(-1-3)]= | | -2p+5=15 | | 30-3x[8-2x(3+1)]= | | -p+5=15 | | cosx=1-m^2 | | -17-(-8)+(-3)-18= | | y=-3(-6)+3 | | 2x+34x=123 | | 9=5y | | -8+-7= | | a+3a=372 | | x^2-x+45=0 | | 4(5y-2)=24 | | 4(3y-1)=5(y+2) | | 3x^3-12x^2-63x=0 |